Alleviation of Phytophthora capsici-induced oxidatıve stress by foliarly applied proline in Capsicum annuum L. - Koç, Esra (Archives of Biological Sciences, 2017)
Phytophthora capsici is a highly destructive pathogen of pepper. To examine whether proline modifies the levels of plant defense compounds produced in response to P. capsici-induced stress, pepper seedlings were infected with P. capsici-22 in the presence of proline (1 mM, 10 mM) or in its absence. Proline was sprayed on the leaves of CM-334 and Kekova pepper cultivars prior to inoculation. CM-334 was more resistant to P. capsici-22, while the Kekova cultivar exhibited a sensitive reaction. P. capsici-22 increased the total phenolic compound and H2O2 levels, as well as phenylalanine ammonia-lyase, polyphenol oxidase and peroxidase activities in pepper seedlings. The application of exogenous proline further increased the activities of phenylalanine ammonia-lyase, polyphenol oxidase and peroxidase, as well as the total levels of phenolic compounds and the fresh and dry weights of the plants on the 5th and 7th days post treatment. After proline application, the highest catalase activity was found in both cultivars on the 5th day of the 10 mM proline + P. capsici application. On all days of the experiment, the applications caused a decrease in disease severity, necrosis length and H2O2 levels in both cultivars. In addition, proline decreased the colony growth of P. capsici and the number of zoospores. This finding indicates that enzymes and total phenolic compound levels protect the pepper seedlings against stress-related damage. Moreover, proline has the potential to directly scavenge free radicals and promote enzyme activity in pepper seedlings under P. capsici stress. These results suggest that foliar application of proline is an effective way to improve the stress tolerance of pepper to P. capsici. https://doi.org/10.2298/ABS160714133K Received: July 14, 2016; Revised: October 22, 2016; Accepted: December 1, 2016; Published online: December 15, 2016 How to cite this article: Koç E. Alleviation of Phytophthora capsici-induced oxidatıve stress by foliarly applied proline in Capsicum annuum L. Arch Biol Sci. 2017;69(4):733-42.